Reading the Country (UTS ePRESS, 2021)
Steeped in story-telling and endlessly curious, Reading the Country: An Introduction to Nomadology (1984) was the product of Paddy Roe, Stephen Muecke and Krim Benterrak, experimenting with what it might be like to think together about country. In the process a senior traditional owner, a cultural theorist and a painter produced a text unlike any other. Reading the Country: 30 Years On is a celebration of one of the great twentieth-century books of intercultural dialogue. Recalling a spirit of intellectual risk and respect, in this collection, Indigenous and non-Indigenous scholars, poets, writers and publishers both acknowledge the past and look, with hope, to future transformations of culture and country.